Justice for Palestine: A Call to Action from Indigenous & Women of Color Feminists - The People's Forum NYC (2021)
We come together on the 10th anniversary of our last day in Palestine, hundreds of presentations, articles, panels, and interventions later, to offer our Report Card reaffirming the relevance and urgency of re-telling stories of apartheid, ethnic cleansing, and settler colonialism and of Palestinian steadfastness, resistance and resilience. SPEAKERS: Dr. Angela Davis Dr. Anna Guevarra Dr. Barbara Ransby Dr. Beverly Guy-Sheftall Dr. Chandra Talpade Mohanty Dr. Gina Dent Dr. G. Melissa Garcia Dr. Rabab Abdulhadi Dr. Waziyatawin Co-sponsored by Arab and Muslim Ethnicities and Diaspora Studies
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; asie; cours; discipline; féminisme autochtone; féminisme décolonial; féminisme islamique; féminismes noirs; génocide; histoire et politique; militance; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; études arabes; études décoloniales

Des ovocytes sous contrôle. Regards franco-suisses sur l’encadrement juridique du don et de l’autoconservation d’ovocytes - Mesnil, Marie (Nouvelles Questions Féministes, 2021)
La comparaison du droit français et suisse concernant le don et l’autoconservation d’ovocytes met en lumière des enjeux en termes de protection de l’intégrité physique, de parenté et de liberté reproductive. Au contraire de la Suisse, la France encadre le don d’ovocytes, mais n’autorise pas l’autoconservation ovocytaire. Pourtant, ces techniques ne remettent pas en cause les normes procréatives et familiales quant au bon âge de la maternité et à la conjugalité hétérosexuelle : les ovocytes - donnés ou conservés - ne peuvent être utilisés que dans le cadre légal d’une procréation médicalement assistée (PMA). L’article examine en détail le projet de loi de bioéthique qui, en France, prévoit d’ouvrir l’autoconservation ovocytaire, mais qui exclut, au sein des couples lesbiens nouvellement éligibles à la PMA, qu’une femme puisse recevoir les ovocytes de sa partenaire. L’auteure met ainsi en avant le fait que le contrôle des corps et de la sexualité des femmes perdure sous des formes renouvelées.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; cours; discipline; discours dominant; droits des femmes*; europe; france; histoire et politique; justice reproductive; maternité; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail; travail reproductif

The feminist political economy of Covid-19: Capitalism, women, and work. - Cohen, Jennifer; van der Meulen Rodgers, Yana (Global public health, 2021)
Analysing the pandemic through a feminist political economy lens makes clear how gender, race, and class structures are crucial to the functioning of capitalism and to understanding the impacts of the pandemic. The way capital organises production and reproduction combines with structures of oppression, generating vulnerability among the racialised and gendered populations worst impacted by Covid-19. Using global data, this commentary shows that during the pandemic, women experienced relatively greater employment losses, were more likely to work in essential jobs, and experienced a greater reduction in income. Women were also doing more reproductive labour than men and were more likely to drop out of the labour force because of it. Analyses of capitalism in feminist political economy illustrate how capital accumulation depends on women's oppression in multiple, fundamental ways having to do with their paid and unpaid work. Women's work, and by extension their health, is the foundation upon which both production and social reproduction rely. Recognising the pandemic as endogenous to capitalism heightens the contradiction between a world shaped by the profit motive and the domestic and global requirements of public health.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; capitalisme; covid-19; histoire et politique; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; violences

Le féminisme décolonial en Abya Yala - Curiel, Ochy; De Roo, Priscilla (Multitudes, 2021)
Les rapports sociaux de race, de genre, de sexe sont inextricablement mêlés : telle est une idée centrale du féminisme décolonial tel qu’il se déploie depuis Abya Yala, du nom que le peuple kuna donnait au continent américain. L’article situe l’importance de renommer les femmes et féministes d’origine autochtone, une manière de défaire les discours coloniaux (parfois tenus par des universitaires féministes) sur les pratiques de genre avant la colonialité/modernité. Ochy Curiel illustre cette idée à partir de l’expérience du GLEFAS (Groupe latino-américain de formation et d’action féministe) : le décolonial n’y est pas seulement une critique du savoir académique, il est profondément ancré dans des pratiques autogestionnaires de luttes anticapitalistes, dans le lesbianisme politique, dans la rue, dans les associations, dans les organisations communautaires.
Keywords: amériques; anthropologie; anthropologie sociale; approches et analyses; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; intersectionnalité; lesbianisme; militance; pol4212; premier cycle; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Women of the great barrier reef: Stories of gender and conservation - Foxwell-Norton, Kerrie; Anderson, Deb; Leitch, Anne M. (Queensland Review, 2021)
In the late 1970s, Carden Wallace was at the beginning of her lifelong exploration of the Great Barrier Reef - and indeed, reefs all over the world. For Wallace, who is now Emeritus Principal Scientist at Queensland Museum, the beginning of her Reef career coincided with the emergence of both feminist and environmental movements that meant her personal and professional lives would be entwined with a changing social, cultural and political milieu. In this article, we couple the story of Wallace's personal life and her arrival in coral science to identify the Reef as a gendered space ripe to explore both feminist and conservation politics. The article is part of a broader Women of the Reef project that supports a history of women's contribution to the care and conservation of the Reef since the 1960s. In amplifying the role of women in the story of the Reef, we find hope in the richness of detail offered by oral history to illuminate the ways discourse on the Reef and its women sits at the intersection of biography, culture, politics and place. In these stories, we recognise women's participation and leadership as critical to past challenges, and to current and future climate change action. By retelling modern Reef history through the experiences and achievements of women, we can develop new understandings of the Reef that disrupt the existing dominance of patriarchal and Western systems of knowledge and power that have led us to the brink of ecological collapse. © The Author(s), 2022.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; approches et analyses; australie; changements climatiques; environnement; histoire et politique; océanie; patriarcat; projet charge mentale; périodes historiques; régions géographiques; rôle des femmes dans la protection de la grande barrière de corail; systèmes d'oppressions; thématiques

La puissance féministe - Gago, Verónica (Éditions de la rue Dorion, 2021)
L’Amérique du Sud est un des coeurs battants du féminisme contemporain. Des millions de femmes y prennent la rue contre les féminicides, les violences qui frappent les minorités de race et de genre, les lois qui répriment l’avortement et le développement néo-extractiviste. Figure majeure du féminisme latino-américain, Verónica Gago réinscrit ces bouleversements dans l’émergence d’une internationale féministe et propose, avec La puissance féministe, un antidote à tous les discours de culpabilité et de victimisation. En se réappropriant l’arme classique de la grève, en construisant un féminisme populaire, radical et inclusif, les mouvements sud-américains ont initié une véritable révolution. C’est à partir de l’expérience de ces luttes que Gago reconceptualise la question du travail domestique et de la reproduction sociale, expose les limites du populisme de gauche et dialogue avec Spinoza, Marx, Luxemburg ou Federici. Parce qu’il unit la verve politique du manifeste aux ambitions conceptuelles de la théorie, La puissance féministe est un livre majeur pour saisir la portée internationale du féminisme aujourd’hui.
Keywords: 2000 à aujourd'hui; amérique latine; amériques; approches et analyses; care; cours; cycles supérieurs; fem7000; histoire et politique; justice sociale; militance; patriarcat; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; violences

Hermeneutical Backlash: Trans Youth Panics as Epistemic Injustice - George, B. R.; Goguen, Stacey (Feminist Philosophy Quarterly, 2021)
In this paper we use the contemporary example of trans youth panics to introduce the notion of hermeneutical backlash, in which defenders of an established, unjust hermeneutical regime actively work to undermine and discredit hermeneutical liberation. We argue that the strategies and tropes of the trans youth panic illustrate a general propaganda vulnerability of epistemic liberation movements (including familiar examples from recent history), and so are troubling for reasons that go beyond their application to trans youth. This exploration of a few specific cases of hermeneutical liberation and hermeneutical backlash calls attention to the need for further theoretical work on the dynamics of struggles for (and against) hermeneutical justice.
Keywords: approches et analyses; backlash herméneutique; cours; cycles supérieurs; discipline; discours dominant; discours médiatique; enfants trans*; fem9000; histoire et politique; hétérosexisme; injustices herméneutiques; militance; philosophie; philosophie féministe; sciences humaines; systèmes d'oppressions; thématiques; transphobie; violences

How far the ecowarrior will go: An ecofeminist reading of disney's Moana - Hernawati, Mala (3L: Language, Linguistics, Literature, 2021)
This article attempts to look into the fictional narrativization of women's significant and distinctive relationship with nature in Disney's Moana. Emphasizing the power and the unity of women and nature in Polynesian indigenous culture, Moana suggests that the destruction of nature results from exploitative and manipulative masculinity. Through ecofeminist perspectives, this essay observes that Moana offers critical views and promotes awareness of gender and environmental issues. These ideas are communicated through the visual and verbal depiction of power relations that defy patriarchal tradition alongside the expressions of protest against devaluation and abuse of nature and women. To put it in the context of the development of themes in Disney's princess line, Moana's presence can be a novel alternative to the typical images of women, namely a new portrayal of a female character whose primary concern is not romance but instead the sustainability of the environment where she lives. This study also confirms that Disney's animated princess films continuously adjust with the dynamics of global feminist discourse. © 2021 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; capitalisme; environnement; film d'animation; féminisme pop; histoire et politique; patriarcat; princesse disney; projet charge mentale; périodes historiques; systèmes d'oppressions; thématiques; écoféminisme

Ces femmes qui ont dit non à la colonisation - Menu, Ève (Éditions Jourdan, 2021)
En 1949 en Côte-d’Ivoire, deux mille femmes marchent d’Abidjan à la prison de Grand-Bassam pour exiger la libération de prisonniers politiques. De 1952 à 1960, des femmes participent massivement à la lutte du peuple kikuyu contre les autorités coloniales au Kenya. Dans les années 1960 au Mozambique, le FRELIMO crée des camps d’entraînement militaire dédiés aux femmes. Aux quatre coins du monde, tout au long de l’histoire de la colonisation, des femmes se sont mobilisées pour résister aux conquêtes, renverser les rapports de force, mettre fin aux discriminations ou arracher la liberté. Partout ou presque, l’histoire a oublié leurs noms. Ce livre veut remettre en lumière une partie de ces oubliées qui ont résisté, pris les armes, ou qui ont milité, manifesté, soigné, nourri, caché. Ces femmes qui ont dit non à la colonisation.
Keywords: approches et analyses; cours; discipline; discours dominant; droits des femmes*; fem3100; femmes* africaines; femmes* afro-descendantes; femmes* autochtones; histoire; histoire et politique; premier cycle; racisme; sciences humaines; systèmes d'oppressions; thématiques; violences

Examining the cracks in universal water coverage: Women document the burdens of household water insecurity - Radonic, Lucero; Jacob, Cara E. (Water Alternatives, 2021)
L’accès universel à l’eau potable est considéré comme une caractéristique déterminante des villes du Nord global. Cet article décrit les défis quotidiens auxquels sont confrontées les femmes de la classe ouvrière de Flint, dans le Michigan, lorsque la promesse d’une infrastructure d’eau moderne se fissure. En 2014, afin de réduire les coûts, la source d’eau potable de Flint a été transférée du lac Huron à la rivière Flint. Ce changement, et plus particulièrement la manière dont il a été géré, a entraîné une contamination de l’approvisionnement en eau par du plomb et des agents pathogènes. Si l’expérience de Flint est désormais un cas emblématique d’insécurité hydrique dans le Nord global, elle n’est pas unique. À travers une étude de cas élaborée dans le cadre d’un projet de recherche participative communautaire, cet article détaille comment l’insécurité hydrique a transféré la charge de l’approvisionnement en eau potable aux ménages individuels, et plus particulièrement aux femmes. Plutôt que de pouvoir compter sur la main-d’œuvre et l’expertise technique qui ont rendu l’eau potable dans la ville moderne, les habitants de Flint ont été soudainement rendus responsables de la sécurité de leur propre approvisionnement en eau. Nous expliquons comment la crise de l’eau de Flint a fait naître une « nouvelle normalité » ; Nous examinons les façons dont cette situation a donné naissance à un nouveau rapport à l'eau potable, caractérisé par un (re)retour à l'eau en bouteille ou filtrée (de l'eau du robinet) et par un changement dans la répartition des tâches nécessaires à la production d'eau potable. Les témoignages de femmes que nous présentons ici illustrent comment, lorsque l'eau uniforme moderne fait défaut, les gens commencent à voir des eaux hétérogènes.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; accès à l'eau potable; amériques; anthropologie; approches et analyses; capitalisme; discipline; eau en bouteille; environnement; histoire et politique; inégalités hommes-femmes; patriarcat; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Pauvreté: récits - Roussel, Stéphanie (Collection Encrages, 2021)
Ce livre est l'histoire de douze textes survivants, rescapés, qui, faute de ressources, auraient pu ne jamais voir le jour. Traversés par le thème de la pauvreté, ces récits troublent le rapport à la famille, à l'éducation, au corps, à la mode, à la nourriture, à la mémoire, à la dette ; les voix, éloquentes et poignantes, s'y font écho autant qu'elles adressent les silences qui persistent.
Keywords: approches et analyses; arts; cours; discipline; histoire et politique; intersectionnalité; inégalités; lit3495; pauvreté; point de vue situé; premier cycle; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Before the “Ecologically Noble Savage”: Gendered representations of Amazonia in the global media in the 1970s - Sarzynski, Sarah (Latin American Perspectives, 2021)
An analysis of media representations of the Amazon and indigenous peoples reveals how media producers and filmmakers foregrounded discourses naturalizing gendered and racialized differences that distinguished the Amazon from the West in the 1970s, a decade during which the Brazilian military dictatorship promoted development projects in Amazonia. These representations often sexualized indigenous peoples and the Amazon itself, portraying them as primitive, cannibal savages, animals or part of nature, or victims of exploitation. The “Othering” of the Amazon and Amazonians was further elaborated through a discourse of binary oppositions that portrayed Western white men as explorers and exploiters who dominated the screen, scripts, studies, and development projects even if they were doomed to fail. By relying on a symbolic system of difference, global media coverage and films about Amazonia in the 1970s were complicit in legitimizing authoritarian decrees promoting large-scale development that depicted indigenous peoples and the environment as obstacles. Un análisis de las representaciones mediáticas de la Amazonía y sus pueblos indígenas revela cómo, en la década de 1970, productores y cineastas mediáticos resaltaron discursos que naturalizaron las diferencias de género y racializadas con las que se distinguían a la Amazonía del Occidente en una época durante la cual la dictadura militar brasileña promovió proyectos de desarrollo en la región. Dichas representaciones a menudo sexualizaban a los pueblos indígenas y a la Amazonía misma, retratándolos como primitivos, caníbales salvajes, animales o elementos naturales, o víctimas de explotación. La “otredad” de la Amazonía y los amazónicos se elaboró a través de un discurso de oposiciones binarias que retrataba a los hombres blancos occidentales como exploradores y explotadores que dominaban la pantalla, los guiones, los estudios y los proyectos de desarrollo, incluso si estos estaban condenados al fracaso. Al confiar en un sistema simbólico de diferencia basado en oposiciones binarias y estereotipos, la cobertura mediática global y las películas sobre la Amazonía en la década de 1970 fungieron como cómplices en la legitimación de los tipos de proyectos y políticas llevados a cabo en la región. © 2021 Latin American Perspectives.
Keywords: amazonie; amériques; approches et analyses; brésil; discipline; domination blanche; domination masculine; histoire; histoire et politique; médias; peuples autochtones; projet charge mentale; racisme; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; violences coloniales; violences racistes; violences sexistes

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Decolonizing methodologies: research and indigenous peoples - Smith, Linda Tuhiwai (Zed Books, 2021)
''To the colonized, the term 'research' is conflated with European colonialism; the ways in which academic research has been implicated in the throes of imperialism remains a painful memory.This essential volume explores intersections of imperialism and research - specifically, the ways in which imperialism is embedded in disciplines of knowledge and tradition as 'regimes of truth.' Concepts such as 'discovery' and 'claiming' are discussed and an argument presented that the decolonization of research methods will help to reclaim control over indigenous ways of knowing and being.Now in its eagerly awaited third edition, this bestselling book includes a co-written introduction features contributions from indigenous scholars on the book's continued relevance to current research. It also features a chapter with twenty-five indigenous projects and a collection of poetry.''-- Site de l'éditeur.
Keywords: approches et analyses; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; militance; méthodologie; méthodologie autochtone; pol4105; premier cycle; pédagogie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; études autochtones

Dead white men vs. Greta Thunberg: Nationalism, misogyny, and climate change denial in swedish far-right digital eedia - Vowles, Kjell; Hultman, Martin (Australian Feminist Studies, 2021)
In the autumn of 2018 Greta Thunberg started her school strike. Soon she and the Fridays For Future-movement rose to world-fame, stirring a backlash laying bare the intrinsic climate change denial of Swedish far-right digital media. These outlets had previously been almost silent on climate change, but in 2019, four of the ten most read articles on the site Samhällsnytt were about Thunberg, all of them discrediting the movement and spreading doubt about climate science. Using the conceptualisation of industrial/breadwinner masculinities as developed by Hultman and Pulé [2018. Ecological Masculinities: Theoretical Foundations and Practical Guidance. Routledge Studies in Gender and Environments. New York: Routledge], this article analyses what provoked this reaction. It explores how the hostility to Thunberg was constructed in far-right media discourse in the years 2018–2019, when she became a threat to an imagined industrial, homogenic and patriarchal community. Using conspiracy theories and historical tropes of irrational femininity, the far right was trying to protect the usually hidden environmental privileges, related to unequal carbon emissions and resource use, that Thunberg and her movement made visible. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discous dominant; environnement; europe; extrême-droite; histoire et politique; misogynie; médias; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; suède; systèmes d'oppressions; thématiques; violences

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences

Antisémitisme et islamophobie. Une histoire croisée - Zia-Ebrahimi, Reza (Contreparties, [2804-9772], 2021)
En France, le seul emploi du mot "islamophobie" provoque des froncements de sourcils, du fait de la campagne soutenue menée par une grande partie de l'intelligentsia et des médias pour le discréditer et nier la réalité objective qu'il propose de décrire. De la même manière, l'idée qu'il puisse exister des similitudes entre l'antisémitisme et l'islamophobie soulève les passions, car elle semble s'attaquer au principe de l'unicité de la Shoah et à la théorie de la "nouvelle judéophobie" . Malgré cette hostilité, les travaux sociologiques et historiques portant sur l'islamophobie moderne ont connu de grandes avancées ces dix dernières années. Beaucoup d'entre eux soulignent que les musulmans sont racialisés, au prétexte non pas de différences morphologiques ou "biologiques" , mais de caractères culturels et religieux. Les juifs d'Europe ayant été le premier groupe religieux à être perçu et représenté comme une race distincte, une étude croisée avec l'antisémitisme s'impose comme l'une des approches les plus adéquates. Ce livre propose une synthèse historique et théorique rigoureuse à l'usage du grand public. Si son objectif principal est d'élucider la relation exacte entre la racialisation du juif et celle du musulman en Occident du milieu du xixe siècle à nos jours, il voudrait également fournir un cadre théorique pour une approche globale des différentes formes de racisme.
Keywords: approches et analyses; cours; discipline; europe; fem3400; histoire; histoire et politique; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences